(untitled) (Revista Brasileira Multidisciplinar, 2020)
The purpose of tissue engineering is to repair, replace, and regenerate tissues and organs. For this aim, materials supports, as polylactic acid (PLA) are used. PLA is a thermoplastic polymer that presents biodegradability, biocompatibility and good processability. PLA scaffolds can accurately constructed by 3D printing. Then, the objectives of this work were to modify the hydrophobic surface of PLA scaffolds using oxygen plasma and to study the cell viability and proliferation. The characterization was done by AFM, contact angle, FTIR and studies of proliferation and cell viability. Results showed that the material acquired hydrophilic properties by the presence of oxygen reactive species and by contact angle decrease. It was also observed an increase in the surface roughness. We can conclude that although the surface modifications were effective and the PLA scaffolds were not cytotoxic, there were no improvements in the proliferation process with the studied osteo-1 lineage cells.